Pelaksanaan Penerimaan Peserta Didik Baru (PPDB) di Madrasah Aliyah (MA) Paradigma Palembang - Febriyanti; Afif Alfiyanto (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
This research is entitled Implementation of New Student (PPDB) in Madrasah Aliyah (MA) Pradigma Palembang. This research uses descriptive qualitative research with data collection techniques using observation, interviews, and documentation. Based on the results of the study, it was analyzed using Sandu Siyoto's opinion which consisted of data reduction, data presentation, and drawing conclusions. From the results of the study, it can be concluded that first, the PPDB implementation process went quite well, it's just that in the promotion of new students, they did not use brochures or social media such as Instagram and YouTube, as well as the school's official website. The promotion process itself has not been conveyed to the public because as a promotional tool such as social media it has not been fully created, an example that is widely used is Youtube, we see now that the era is getting more advanced, of course MA Paradigma must have a Youtube, Instagram, Facebook account and so on. Second, the supporting factors in the implementation of new student recruitment are alumni, strategic school locations, teacher quality and extracurricular activities. While the inhibiting factors in the implementation of new student recruitment are alternative schools, inadequate facilities and infrastructure, building development that is not possible, and status as a private school.